Export price and local price relation in longan of Thailand: The bivariate threshold vecm model - Nachatchapong Kaewsompong (2019)
© Springer Nature Switzerland AG 2019. There is an evidence of non-linear long-run equilibrium relationship between local longan price and all export longan price variables in Thailand. This paper examines the short run and long run relationship between the Thai local longan price and various export longan prices using a Threshold VECM Model. We used the monthly data for the period of 2005M1 to 2013M3. The threshold co-integration test confirms the non-linear long-run equilibrium relationship between local longan price and all export longan price variables. Also, we found the existence of long run equilibrium in local price relation with other export prices when the value of the error-correction is greater than the threshold level. Our results confirm that the longan market is cointegrated and it tends to be efficient and competitive when the longan market price is high.